What do Science Teachers Notice in the K12 Learner’s Material Produced by State Education Department? - Alagadan, Marc Engelbert R.; Rogayan Jr, Danilo V.; Dacayo, Jonalyn C. (Future Science / FSH-PH Publications, 2023)
Learning materials aid conceptual retention, stir learning motivation, increase academic engagement, and enhance student achievement. This study is a descriptive-evaluative research that described the science teachers’ assessment of the Grade 8 Science K12 learner’s material produced by the state education department. The study was conducted in three government-owned secondary schools in Zambales, Philippines. The science teachers used a modified Learning Resource Assessment Tool developed by Prince Edward Island (2008) in evaluating the K12 material. Results revealed that the learner’s material is satisfactory in terms of content, instructional design, and technical design. However, the teachers cited some problems encountered, such as inadequacy of the materials for the learners, the incongruence of the topics to the learning competencies, and lack of instructional time to cover all the topics. The teachers also laid some recommendations that can be forwarded to the Department of Education to review, refine, revise and re-align the learner’s material to make it research-based, relevant, and responsive to the learners' needs.